Breach Remedies, Performance Excuses, and Investment Incentives - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
Contract law is usually perceived as a strict liability system. When a promisor fails to perform he is held liable even if he is without fault. If, however, an unusual contingency has arisen he may be excused from performing provided that he has taken reasonable precautions. For a setting with uncertain costs of and benefits from performance, it is shown that a fixed price contract is sufficient to generate efficient reliance and precautions incentives under the following legal regime. If the promisor has met the appropriate precaution standard then he is excused if performance fails to be profitable. Alternative regimes, in contrast, where he is excused if performance is inefficient or even is extremely costly distort investment incentives quite generally.
urn:nbn:de:bvb:19-epub-13305-4
Keywords: K12; 330; performance excuse; impracticability doctrine; overreliance; efficient precaution